The Machine Learning Paradigms - Shreya B. Ahire, Dhanashree S. Tayade (International Journal of Advanced Science and Technology, 2020)
Machine learning is one of the newest technologies of artificial intelligence. It has made several improvements in the past few decades. Under machine learning many paradigms are available. These paradigms are applicable in various areas such as Virtual Personal Assistants, Videos Surveillance, Social Media Services, Healthcare. In this paper most popular Machine learning paradigms are discussed along with applications. The main intention is to provide information to choose appropriate machine learning model.